Analisis Faktor Yang Mempengaruhi Keputusan Pemilihan Jurusan Pariwisata Di Universitas Pertiwi: Analysis of Factors Influencing the Decision to Choose a Tourism Major at Pertiwi University - Farrah Munif; Muhammad Yafi; Miftahudin (Jurnal Bisnis dan Ekonomi, 2025)
Objective: This study aims to identify and analyze the factors influencing the decision to major in tourism at Pertiwi University and identify the most influential factors.   Methodology: Based on the research problem, this study is a descriptive study using a survey method. The sample size for this study was 60 students majoring in tourism at Pertiwi University. Sampling was conducted using a purposive sampling technique. The research instrument was an online questionnaire with a five-point Likert scale. Data were analyzed by measuring the percentage of respondents who responded to the survey.   Research Results: The results indicate that interest, personality, and job opportunities were 93% likely to agree that these factors influenced the decision to major in tourism at Pertiwi University. Another factor, university reputation, was 92% likely to influence the decision to major in tourism at Pertiwi University.